Dynamic balance performance of professional turkish soccer players by playing position - Ates, B. A. (Physical Education of Students, 2019)
Background and Study Aim: Balance control has been regarded as a crucial factor in sports and indicated as an important element to be examined for the risks of injury. But it is unknown whether the dynamic balance changes according to the player positions in professional soccer players. To determine whether there were differences in the dynamic balance performance of the different positions of Turkish professional soccer players from within one squad. Material and Methods: Twenty-four professional soccer players were divided into 4 groups by the coach, including goalkeepers (n = 3), midfielders (n = 6), defenders (n = 7) and forwards (n = 8). Prior the competition season, anthropometric characteristics of players were measured. Then, players were tested Y Balance Test (YBT) for the anterior (ANT), posteromedial (PM), and posterolateral (PL) reach distances and limb lengths bilaterally. Results: The goalkeepers were heavier compared with the midfielders. Furthermore, the BMI of the goalkeepers were higher than midfielders and defenders (p< 0.05). There were no significant differences in the ANT, PM, PL, and COMP score between the groups (p> 0.05). The values for reach asymmetry were lower than four centimeters among groups in the all reach direction with regards to reach asymmetries, except normalized posterolateral direction. Conclusions: The results of this study have shown that the YBT performance scores do not differ between the groups. Future studies are required to create specific norms related to dynamic balance performance and establish risk cut-off score for professional soccer players.